2016
DOI: 10.1002/hbm.23369
|View full text |Cite
|
Sign up to set email alerts
|

Creative females have larger white matter structures: Evidence from a large sample study

Abstract: The importance of brain connectivity for creativity has been theoretically suggested and empirically demonstrated. Studies have shown sex differences in creativity measured by divergent thinking (CMDT) as well as sex differences in the structural correlates of CMDT. However, the relationships between regional white matter volume (rWMV) and CMDT and associated sex differences have never been directly investigated. In addition, structural studies have shown poor replicability and inaccuracy of multiple compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 97 publications
(223 reference statements)
1
25
0
Order By: Relevance
“…In the male group, the ΔFC components correlated with CS were Our observation of a gender-based difference in CS-ΔFC is consistent with other studies reporting a gender-based difference in neuroimaging studies of the resting state (Filippi et al, 2013) as well as during cognitive tasks (Bell et al, 2006;Hill et al, 2014;Speck et al, 2000). Gender differences in both the structural and function neuroimaging correlates of creativity have also been reported (Abraham, 2016;Abraham et al, 2014;Ryman et al, 2014;Takeuchi et al, 2017aTakeuchi et al, , 2017b and such gender-based differences have also been observed in EEG studies (Fink & Neubauer, 2006;Razumnikova, 2004). Apart from suggesting that females and male TTCT creativity scores are mediated by different patterns of cortical networks, these findings also suggest that caution should be exercised in pooling male and female participants as such pooling will dilute significant gender differences.…”
Section: Creativity Score Is Correlated With Brain Functional Connesupporting
confidence: 90%
See 1 more Smart Citation
“…In the male group, the ΔFC components correlated with CS were Our observation of a gender-based difference in CS-ΔFC is consistent with other studies reporting a gender-based difference in neuroimaging studies of the resting state (Filippi et al, 2013) as well as during cognitive tasks (Bell et al, 2006;Hill et al, 2014;Speck et al, 2000). Gender differences in both the structural and function neuroimaging correlates of creativity have also been reported (Abraham, 2016;Abraham et al, 2014;Ryman et al, 2014;Takeuchi et al, 2017aTakeuchi et al, , 2017b and such gender-based differences have also been observed in EEG studies (Fink & Neubauer, 2006;Razumnikova, 2004). Apart from suggesting that females and male TTCT creativity scores are mediated by different patterns of cortical networks, these findings also suggest that caution should be exercised in pooling male and female participants as such pooling will dilute significant gender differences.…”
Section: Creativity Score Is Correlated With Brain Functional Connesupporting
confidence: 90%
“…We propose to test the abovementioned hypothesis separately in both a male and female group of participants. While the majority fMRI-based neuroimaging studies of creativity have reported results based on mixed gender groups (Beaty et al, 2014(Beaty et al, , 2015(Beaty et al, , 2016(Beaty et al, , 2018Gonen-Yaacovi et al, 2013;Jung et al, 2013;Kounios et al, 2008) and thus not designed to address possible gender effects, some structural and functional neuroimaging studies have reported significant gender differences in the neuroanatomical and activation correlates of creativity (Abraham, 2016;Abraham, Thybusch, Pieritz, & Hermann, 2014;Ryman et al, 2014;Takeuchi et al, 2017aTakeuchi et al, , 2017b. Such gender differences have also been reported in terms of structural connectivity (Ingalhalikar et al, 2014) as well as a range of cognitive tasks (AlRyalat, 2017;Bell, Willson, Wilman, Dave, & Silverstone, 2006;Cahill, 2006;Hill, Laird, & Robinson, 2014;Zaidi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The present study is a part of an ongoing project to investigate associations among brain structure and activity, cognitive function, and aging. Recent work includes studies on VBM (Takeuchi et al, 2017a) and resting-state activity (Ikeda et al, 2017;Takeuchi, Taki, et al, 2017). Therefore, subjects in this study have received psychological tests and MRI scans aside from those described in the present report.…”
Section: Subjectsmentioning
confidence: 99%
“…Only a few studies have examined how white matter structural connectivity relates to creative ability (Jung, Grazioplene, Caprihan, Chavez, & Haier, 2010; Jung et al, 2013; Ryman et al, 2014; Takeuchi et al, 2017; Takeuchi et al, 2010, 2011; Wu, Zhong, & Chen, 2016). Takeuchi et al (2010) conducted a diffusion tensor imaging study to examine the relation between white matter integrity (measured with fractional anisotropy) and creative ability.…”
Section: Introductionmentioning
confidence: 99%